Jig design for reduction of assembly cycle time and defect for front panel assembly - Siti Aishah Binti Mohamad Mukhtar (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
Problems that often occur when the assembly process is high assemcly time and defect are serious problem that occurs in every production industry.To complete the assembly process of front panel at Wong Engineering thesame problem happen which is the cycle time too long and defect frequently happens during assembly the front panel. The problems happens because the procees of assembly without a suitable tool to guide the worker. Beside that, the exising assembly process does not use the right process instuction. Therefore, the objective of this study is to design a tool to reduce defects and cycle time.